Cash holdings and corporate financialization: Evidence from listed Latin American firms - Rabinovich, Joel; Perez Artica, Rodrigo (Competition & Change)
The increase in cash holdings held by non-financial corporations in emerging economies in general, and Latin American in particular, has received less attention vis-à-vis their advanced economies? peers. Considering that cash holdings contain not only cash but also short-term, interest-bearing assets, we test whether the pursuit of financial revenues was one motive behind the decision to hold this type of asset as it is claimed in analyses of corporate financialization. We use a panel of listed non-financial firms from Argentina, Brazil, Chile, Mexico, and Peru between 1998 and 2018 to test this hypothesis. Although we find supporting statistical evidence in favor of this relation, this is mostly explained by Brazil and results point towards a low economic significance. Fil: Rabinovich, Joel. City University of London; Reino Unido. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Perez Artica, Rodrigo. Consejo Nacional de Investigaciones Cientificas y Tecnicas. Centro Cientifico Tecnologico Conicet - Bahia Blanca. Instituto de Investigaciones Economicas y Sociales del Sur. Grupo Vinculado de la Localidad de Pigue | Universidad Nacional del Sur. Departamento de Economia. Instituto de Investigaciones Economicas y Sociales del Sur. Grupo Vinculado de la Localidad de Pigue.; Argentina